From Worms to Drug Candidate: The Story of Odilorhabdins, a New Class of Antimicrobial Agents - Racine, Emilie; Gualtieri, Maxime (Frontiers in Microbiology, 2019)
A major issue currently facing medicine is antibiotic resistance. No new class of antibiotics for the treatment of Gram-negative infections has been introduced in more than 40 years. We screened a collection of Xenorhabdus and Photorhabdus strains in the quest to discover new structures that are active against the most problematic multidrug-resistant bacteria. These species are symbiotic bacteria of entomopathogenic nematodes and their life cycle, the richness of the bacteria’s genome in NRPS and PKS genes, and their propensity to produce secondary metabolites with a large diversity of chemical structures make them a good starting point to begin an ambitious drug discovery program. Odilorhabdins (ODLs), a novel antibacterial class, were identified from this campaign. These compounds inhibit bacterial translation by binding to the small ribosomal subunit at a site not exploited by current antibiotics. Following the development of the total synthesis of this family of peptides, a medicinal chemistry program was started to optimize their pharmacological properties. NOSO-502, the first ODL preclinical candidate was selected. This compound is currently under preclinical development for the treatment of multidrug-resistant Gram-negative infections in hospitalized patients.